Design of a microcontroller-based passive standby uninterruptible power suply (UPS) - Nik Mohamad Anis, Nik Haron (2008)
Uninterruptible Power Supply (UPS) are widely used to provide emergency power to critical loads in case of utility mains failure, and as such constitutes an essential element in providing back-up power for computer networks, communication links, biomedical equipment, and industrial processes, among others. For a microcontroller-based UPS, a full hardware-based UPS are gradually being replaced by microprocessor or microcontroller-based counterparts, with significant improvement in ease of design, flexibility of the control software and overall reduction in development cost. Since a UPS incorporates a relatively large number of detection, protection and control functions, it is important to develop an organized approach to the identification and implementation of these requirements. The purpose of his project is to provide an efficient time management for users to continue their work with personal computer even though an outage had occurred. Since this project involves hardware-software co-design, so that knowledge from a number of engineering disciplines is necessary for arriving at a workable solution. This microcontroller-based Uninterruptible Power Supply will enable the users to monitor their current battery level through the installed Liquid Crystal Display. One of the advantages applying microcontroller for the Uninterruptible Power Supply is that the system is more reliable in functions compares to the conventional Uninterruptible Power Supply available in the market.